Advances in Management of Food Allergy in Children - Chiera, Fernanda; Caminiti, Lucia; Crisafulli, Giuseppe; Pajno, Giovanni B. (Current Pediatric Reviews, 2020)
Food allergy is a potentially life-threatening medical condition and a significant public health concern worldwide. The current management consists of strict avoidance of the culprit food and treating any adverse reactions from unintended food ingestion. The increasing prevalence of food allergy encouraged research and clinical trials in the field of specific allergen immunotherapy (AIT) which represents an appealing approach, especially in pediatric age. AIT consists of the gradual administration of growing amounts of the offending allergen in order to induce food desensitization, which is an increase in the threshold for reactivity while continuing on regular exposure to the allergen. AIT can be administered through oral, sublingual, epicutaneous, and subcutaneous routes. Reports on oral immunotherapy (OIT) thus far have been more extensive. The desirable goal is to achieve
Keywords: modified proteins